Information Computing and Applications Second International Conference, ICICA 2011, Qinhuangdao, China, October 28-31, 2011. Proceedings, Part II - Liu, Chunfeng; Chang, Jincai; Yang, Aimin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set, CCIS 243 and CCIS 244, constitutes the refereed proceedings of the Second International Conference on Information Computing and Applications, ICICA 2010, held in Qinhuangdao, China, in October 2011. The 191 papers presented in both volumes were carefully reviewed and selected from numerous submissions. They are organized in topical sections on computational statistics, social networking and computing, evolutionary computing and applications, information education and application, internet and web computing, scientific and engineering computing, system simulation computing, bio-inspired and DNA computing, internet and Web computing, multimedia networking and computing, parallel and distributed computing.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Software engineering; Information theory; Computer software; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Software Engineering/Programming and Operating Systems; Theory of Computation; Computer Systems Organization and Communication Networks